STUDI SIFAT FISIS BATUAN PADA DAERAH RAWAN LONGSOR - Rahmaniah -; Andi Armayani - (Teknosains, 2013)
This research concerning the study of the nature of fisis rocks at the gristle landslide parangloe, sub-district district gowa, south sulawesi. The study is done at home, lonjoboko parangloe sub-district district gowa, south sulawesi the analysis of samples conducted in laboratories physics and soil fertility gambir-solo agriculturist agriculture, faculties hasanuddin, university makassar. On this research kinds of analysese soil types, mass as levels of ground water and determination texture. Of research have done, obtained based on the conclusion that the soil texture in clay and domination by mineral gristly; a mass of type, which many binding water and relatively high water levels the research indicates that this has the potential danger landslide.